Molecular Genetics In Opiotd Addictions - Khairi, Che Mat; Nasir, Mohamad; Liyana Hazwani, Mohd Adnan (2014)
Opiate addiction is a chronically relapsing disorder that is characterized by compulsive drug-seeking behavior without the ability to limit their intake (De Vries and Shippenberg, 2002). Humans have used opiate drugs such as morphine and heroin for thousands of years to lessen their pain and produce euphoria. These drugs, originally derived from the juice of the opium poppy, have many benefits -- but they also produce adverse side effects like addiction. It becomes a major problem in our society where many of the complex diseases are associated with the opiate addiction, for example human immunodeficiency virus infection, hepatitis B and C infection, depressive and anxiety disorders and other psychiatric illnesses (Kreek, 1996).